The Influence of Spiritual Well-being of Life Satisfaction: Self Esteem as a Mediator - Russ, Najwa Mat; Rosli , Noor Aishah; Tharbe, Ida Hartina Mohd. (International Journal of Psychosocial Rehabilitation, 2020)
This study examines the relationship between spiritual well-being and self-esteem that ultimately affects life satisfaction. A total of 383 respondents were selected to participate in this research through cluster sampling from all over Selangor. The study followed a quantitative research design to investigate the degree of relationship between spiritual well-being, self-esteem and life satisfaction. Data were analysed through confirmatory factor analysis (CFA) using AMOS. The findings of this study corroborate that spiritual well-being is observed to have impacts on life satisfaction. At the same time, SEM analysis found significant influences of spiritual well-being on self-esteem. The indirect effects of spiritual well-being were observed on life satisfaction via self-esteem as a full mediator. The findings imply that self-esteem appear to be crucial in the relationship between spiritual well-being and life satisfaction.